2001
DOI: 10.1136/oem.58.7.461
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from cardiovascular diseases and exposure to inorganic mercury

Abstract: Objective-To study the mortality from cardiovascular and other chronic nonneoplastic diseases after long term exposure to inorganic mercury. Limited information is available on the eVect of chronic exposure to mercury on the cardiovascular system. Methods-The mortality was studied among 6784 male and 265 female workers from four mercury mines and mills in Spain, Slovenia, Italy, and the Ukraine. Workers were employed between 1900 and 1990; the follow up period lasted from the 1950s to the 1990s. The mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 16 publications
0
44
1
4
Order By: Relevance
“…An increased mortality (in comparison to national reference rates) from hypertension and heart diseases other than ischaemic was found. Mortality from hypertension was increased with estimated cumulative exposure to mercury; mortality from ischaemic heart disease and cerebrovascular events increased with duration of employment [13]. Also an increased risk of cardiovascular mortality, especially due to hypertension or cerebrovascular pathology, was shown in a follow-up study in workers exposed to mercury in Minas de Almadény Arrayanes in Spain [14].…”
Section: The Studied Groupmentioning
confidence: 99%
“…An increased mortality (in comparison to national reference rates) from hypertension and heart diseases other than ischaemic was found. Mortality from hypertension was increased with estimated cumulative exposure to mercury; mortality from ischaemic heart disease and cerebrovascular events increased with duration of employment [13]. Also an increased risk of cardiovascular mortality, especially due to hypertension or cerebrovascular pathology, was shown in a follow-up study in workers exposed to mercury in Minas de Almadény Arrayanes in Spain [14].…”
Section: The Studied Groupmentioning
confidence: 99%
“…However, few data are available on the effect of mercury on heart and aorta tissues (Boffetta et al, 2001;Moreira et al, 2003). Inorganic mercury is conjugated with glutathione in the liver and secreted in the bile as a cysteine mercury or glutathione mercury complex (Boffetta et al, 2001). Numerous studies have demonstrated that Hg causes lipid peroxidation (Lund et al, 1991;Yonaha et al, 1980), DNA damage (Lund et al, 1991;Yonaha et al, 1980), porphyrinogen oxidation (Woods et al, 1990;Woods and Ellis, 1995) and depletion of reduced glutathione (Gstraunthaler et al, 1983;Sener et al, 2003), which support an oxidative stress-like mechanism for Hg(II) toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of high doses of inorganic mercury on the central nervous system and urinary system has been known for decades (Patrick, 2002). However, few data are available on the effect of mercury on heart and aorta tissues (Boffetta et al, 2001;Moreira et al, 2003). Inorganic mercury is conjugated with glutathione in the liver and secreted in the bile as a cysteine mercury or glutathione mercury complex (Boffetta et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…e increase in death from hypertension was present only in Spain, and in Ukraine, whereas a decrease in the risk of this disease was found in the other countries. An increased mortality from cardiovascular diseases was apparent according to time since �rst exposure [87].…”
Section: Mortality From Cardiovascularmentioning
confidence: 99%